1985
DOI: 10.1172/jci111679
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of myeloid progenitor cells after "successful" bone marrow transplantation.

Abstract: IntroductionWe studied recovery of peripheral blood-and bone marrowderived myeloid progenitor cells (CFU-G,M) T cell depletion with a monoclonal anti-T antibody (B7) and complement had no effect. These data indicate that most transplant recipients have a marked abnormality in CFU-G,M when these cells are cultured in vitro. In at least some of these patients, the decreased cloning efficiency of CFU-G,M appears to be mediated by a suppressive effect of autologous T cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0
2

Year Published

1986
1986
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 27 publications
2
15
0
2
Order By: Relevance
“…[46][47][48][49] While the precursor frequencies increased over time in recipients post transplant, they rarely ever returned to normal levels, continuing to remain 20-40% of that of the donor population even 3 years later. 49 In patients undergoing autologous stem cell transplant, CFU-GMs and erythroid burst-forming units (BFU-E) may take up to 2 years to reach pre-graft levels, erythroid CFUs (CFU-E) up to 4 years to recover, and megakaryocyte CFUs (CFU-Meg) even longer.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48][49] While the precursor frequencies increased over time in recipients post transplant, they rarely ever returned to normal levels, continuing to remain 20-40% of that of the donor population even 3 years later. 49 In patients undergoing autologous stem cell transplant, CFU-GMs and erythroid burst-forming units (BFU-E) may take up to 2 years to reach pre-graft levels, erythroid CFUs (CFU-E) up to 4 years to recover, and megakaryocyte CFUs (CFU-Meg) even longer.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a reduced number of committed progenitor cells despite normal peripheral blood cell counts has been described after both allogeneic 4,19,20 and autologous bone marrow transplantation. 5,6,21 It is already well known that there is a correlation between the number of cycles of radio/chemotherapy and depletion of the stem cell compartment.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of authors have found a decrease in colony-forming unit (CFU-C) levels in both allogeneic and autologous bone marrow recipients (ABMT) a long time after transplant (up to 8.5 years). 4,5 Domenech et al 6 found an impairment in the long-term cultures of 33 patients after autologous bone marrow transplantation: the defect involved both CFU-C output and stromal cell formation. Using different techniques, van den Berg et al 7 and O'Flaherty et al 8 clearly demonstrated that a stromal cell compartment defect is always present after allogeneic bone marrow transplantation.…”
mentioning
confidence: 99%
“…13 Abnormalities in haematopoiesis have been shown following transplantation. [14][15][16][17] Decreased bone marrow cellularity has been shown to persist up to 3 years following allogeneic transplantation. 18 The number of colony-forming units (CFU-GM, BFU-E, CFU-Meg and TL-CFU) was shown to be diminished following autologous transplantation persisting for as long as 4-5 years.…”
mentioning
confidence: 99%